Do volatile firms pay volatile earnings? Evidence using linked worker-firm data - Michael R. Strain (American Enterprise Institute (AEI), 2013)
The instability of labor earnings in the United States contributes to earnings inequality and may diminish household welfare. Despite the importance of earnings instability little is known about its correlates or causes. This paper seeks to better understand earnings instability by studying whether volatile firms pay volatile earnings. I am the first to directly test the relationship between earnings instability and firm employment instability using linked employer-employee data. I find a positive and statistically significant relationship between the two that remains when the effect is estimated using only within-firm variation. This suggests that the effect is a feature of the way workers are being paid by their employer. The size of the effect varies by a worker's position in the earnings distribution: low-earning workers are passed a greater share of firm employment instability than higher-earning workers. Survey data from the NLSY79 confirm that lower-skill workers have relatively less stable earnings. I find significant heterogeneity in the magnitude and significance of the effect across industries and explore how the competitiveness of an industry relates to the size of the industry specific effect.
Keywords: J; 330; Labor economics